Research on the Application of Deep Learning in Fire Warning of New Energy Vehicles - Pan, Dongyan; Xu, Zili; Pan, Jun (Scientific Journal of Technology, 2025)
With the enhancement of environmental awareness in countries around the world, new energy vehicles, as a new type of green transportation mode, are receiving increasing attention. However, the safety issues of new energy vehicles, especially fire safety, have drawn extensive attention from all sectors of society. Compared with traditional fuel vehicles, the power systems and energy storage systems of new energy vehicles are more complex. In particular, battery packs are highly prone to causing fires under conditions such as high temperatures, overcharging, and short circuits. Once a fire breaks out, it not only causes severe damage to the vehicle itself, but also threatens the lives of passengers and seriously endangers the surrounding environment and public safety. Therefore, how to effectively prevent and warn of fires in new energy vehicles is an important issue to ensure their safe operation.